FRACTIONATION AND THERMAL CHARACTERIZATION OF HEMICELLULOSES FROM BAMBOO (PHYLLOSTACHYS PUBESCENS MAZEL) CULM - Hong Peng; Zhengrong Hu; Ziping Yu; Jinsheng Zhang; Yuhuan Liu; Yiqin Wan; Roger Ruan (BioResources, 2011)
Water-soluble hemicelluloses and eight alkali-soluble hemicelluloses were fractionated from bamboo (Phyllostachys pubescens Mazel) culm with hot distilled water, 2% NaOH, 2% KOH, 5% NaOH, and 5% KOH aqueous solution. The chemical structures, as analyzed employing FTIR spectrometry, suggested that all the hemicelluloses were likely to be comprised of arabinoxylans associated with lignin more or less. Thermal analysis for hemicelluloses was carried out using TG-DTG method under nitrogen atmosphere at a heating rate of 10 C/min, and first-order kinetics was evaluated. The major pyrolysis was focused at 187-346 C, with activation energy ranging from 23.77 to 45.02 kJ/mol. The alkali-soluble fractions, being soluble in solution only at pH higher than 5.5, presented lower thermal stability and higher values of activation energy and pre-exponential factor than the alkali-soluble fractions remaining soluble in alkaline solution at pH lower than 5.5 and insoluble in ethanol. The chemical property of the hemicellulose fractions may greatly influence the thermal characteristics.